Description of hitherto unknown female genitalia of Crossotocera wagnerella Zerny, 1930, in Wagner (Lepidoptera: Oecophoridae) - Jan Sumpich; Ignac Richter (SHILAP, 2023)
This paper describes the female genitalia of Crossotocera wagnerella Zerny 1930, in Wagner, 1930 for the first time. Photographs of adults as well as of the genitalia of both sexes are provided, and first records from North Macedonia are reported.